How to deal with heterogeneity among tourism constructs?. (May 2015) - Marques, Catarina; Reis, Elizabeth
Highlights: Analyzing the effects of unobserved heterogeneity in Structural Equation Modeling. Uncovering unobserved heterogeneity and segments by a finite-mixture approach. Examining how environmental attitudes influence the preference for outdoor activity. Model estimation in a nature-based tourism context using PLS Path Modeling.